1995
DOI: 10.1080/09540109509354873
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐idiotype and anti‐anti‐idiotype antibodies generated from polyclonal antibodies against aflatoxin b1

Abstract: Polyclonal anti-idiotype antibodies pAb2) for aflatoxin were generated from mice ascites after immunization with affinity-purified rabbit polyclonal antibody (pAbl) against aflatoxin B 1 (pAFB 1 ). After affinity chromatography purification, pAb2 were subjected to various analyses, and were used to generate anti-anti-id antibodies (pAb3) in the ascites of Balb/c mice. ELISA analyses revealed that the anti-id antibodies bound specifically to the original pAb1, but not to other types of monoclonal antibodies o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 27 publications
2
5
0
Order By: Relevance
“…Such properties are similar to recent observations for the anti-id antibodies generated in rabbits and mice (Hsu & Chu, 1994, 1995, as well as data obtained from studies for the anti-id antibodies of several other hapten-type toxins and insecticides (Chanh et al, 1990;Shestowsky et al, 1992;Spinks et al, 1993). Whereas IgY2 appear to have little use in the immunoassay of aflatoxins, IgY2 could be used as a good immunogen in generating the Ab3 as in previous studies (Hsu & Chu, 1994, 1995. In the present study, IgY3 were generated in chickens after immunization of rabbit pAb2 that were induced by immunizing with anti-AFB 3 -HS-BSA monoclonal antibodies.…”
Section: Production and Characterization Of Egg Yolk Igy3supporting
confidence: 87%
See 3 more Smart Citations
“…Such properties are similar to recent observations for the anti-id antibodies generated in rabbits and mice (Hsu & Chu, 1994, 1995, as well as data obtained from studies for the anti-id antibodies of several other hapten-type toxins and insecticides (Chanh et al, 1990;Shestowsky et al, 1992;Spinks et al, 1993). Whereas IgY2 appear to have little use in the immunoassay of aflatoxins, IgY2 could be used as a good immunogen in generating the Ab3 as in previous studies (Hsu & Chu, 1994, 1995. In the present study, IgY3 were generated in chickens after immunization of rabbit pAb2 that were induced by immunizing with anti-AFB 3 -HS-BSA monoclonal antibodies.…”
Section: Production and Characterization Of Egg Yolk Igy3supporting
confidence: 87%
“…In the present study, IgY3 were generated in chickens after immunization of rabbit pAb2 that were induced by immunizing with anti-AFB 3 -HS-BSA monoclonal antibodies. Similar to the pAb3 obtained from rabbits (Hsu & Chu, 1994) and mice (Hsu & Chu, 1995) after immunizing with pAb2, IgY3 obtained from this study have also been shown to be useful for the ELISA of aflatoxins. The sensitivity of the present IgY3-based ELISA for AFBi was found to be comparable with most of the pAbl-and mouse pAb3-based ELISAs.…”
Section: Production and Characterization Of Egg Yolk Igy3mentioning
confidence: 81%
See 2 more Smart Citations
“…This situation has been alleviated to some extent by the development of immunological methods and the production of monoclonal antibodies (Morgan and Lee 1990). In efforts to increase the sensitivity of these methods Hsu and Chu (1995) generated anti-idiotype and anti-anti-idiotype antibodies from polyclonal antibodies against aflatoxin B 1 . Immunological reagents can be used in two modes, for direct analysis by ELISA after extraction, or in the clean-up stages in the form of affinity columns.…”
Section: Recent Analytical Developmentsmentioning
confidence: 99%